Prevalensi Ektoparasit Pada Kucing di Klinik Hewan Winadivet Malang - Tetty Barunawati Siagian; Ikfa Sulkhan Hadi; Winda Syafitri (Jurnal Biologi Universitas Andalas, 2023)
AbstractCats are domesticated animals whose existence is very close to humans. Maintenance of the wrong cat will cause the risk of zoonotic diseases. to humans caused by ectoparasites. Ectoparasites in cats are fleas, mites, and fleas. Information regarding the prevalence of ectoparsite infestation in cats can be used as a preventive measure. The purpose of this final report is to explain the prevalence of ectoparasites in cats at the Winadivet Animal Clinic in Malang. Prevalence sample examination was carried out on 156 cats divided into 7 breeds, namely Domestic, Persian, Bengal, British Short Hair, Peaknose, Anggora, Himalayan who came to the clinic during April 2021. Examination was carried out macroscopically and microscopically, microscopic method using native method. The results of the examination found 45 cats that were positively infected with ectoparasites, namely the Ctenocephalides felis flea, Felicola subrostatus fleas, Otodectes cynotis mites, and Sarcoptes scabei. The prevalence of infestation obtained was 28.8%. The highest prevalence of ectoparasites in purebred cats is in domestic cats with a prevalence value of Ctenocephalides felis 12.7%, Felicola Subrostatus 5.1%, Otodectes cynotis 3.2%, Sarcoptes scabei 0.6%. Factors that influence the high prevalence are environment, temperature, humidity, maintenance, and direct contact from infected animals.